(untitled) (The Pakistan Development Review, 2013)
“The Culture of Power and Governance of Pakistan 1947–2008” by Ilhan Niaz makes a strong case for the quotation, “the one who does not remember history is bound to live through it”. In the book, the author has tried to trace the current culture of power and governance in Pakistan through the rich history of the subcontinent. He has asked the question that why the State of Pakistan is constantly losing its writ as many incidents, such as the “Laal Masjid” debacle, are challenging the writ of the state. He has also analysed why State of Pakistan is always facing issues in domains of administration, legislation, execution and judiciary. These issues are becoming existential threat to the Pakistani State. The author has blamed the rulers of Pakistan who behave like “Bureaucratic Continental Empires”.